Mice Lacking the Inhibitory Collagen Receptor LAIR-1 Exhibit a Mild Thrombocytosis and Hyperactive Platelets. Issue 5 (May 2017) - Smith, Christopher W.; Thomas, Steven G.; Raslan, Zaher; Patel, Pushpa; Byrne, Maxwell; Lordkipanidzé, Marie; Bem, Danai; Meyaard, Linde; Senis, Yotis A.; Watson, Steve P.; Mazharian, Alexandra
Abstract : Objective—: Leukocyte-associated immunoglobulin-like receptor-1 (LAIR-1) is a collagen receptor that belongs to the inhibitory immunoreceptor tyrosine-based inhibition motif–containing receptor family. It is an inhibitor of signaling via the immunoreceptor tyrosine-based activation motif–containing collagen receptor complex, glycoprotein VI-FcRγ-chain. It is expressed on hematopoietic cells, including immature megakaryocytes, but is not detectable on platelets. Although the inhibitory function of LAIR-1 has been described in leukocytes, its physiological role in megakaryocytes and in particular in platelet formation has not been explored. In this study, we investigate the role of LAIR-1 in megakaryocyte development and platelet production by generating LAIR-1–deficient mice. Approach and Results—: Mice lacking LAIR-1 exhibit a significant increase in platelet counts, a prolonged platelet half-life in vivo, and increased proplatelet formation in vitro. Interestingly, platelets from LAIR-1–deficient mice exhibit an enhanced reactivity to collagen and the glycoprotein VI–specific agonist collagen-related peptide despite not expressing LAIR-1, and mice showed enhanced thrombus formation in the carotid artery after ferric chloride injury. Targeted deletion of LAIR-1 in mice results in an increase in signaling downstream of the glycoprotein VI–FcRγ-chain and integrin αIIbβ3 in megakaryocytes because of enhanced Src family kinase activity. Conclusions—: Findings from this study demonstrate that ablation of LAIR-1 in megakaryocytes leads to increased Src family kinase activity and downstream signaling in response to collagen that is transmitted to platelets, rendering them hyper-reactive specifically to agonists that signal through Syk tyrosine kinases, but not to G-protein–coupled receptors. Abstract : Supplemental Digital Content is available in the text.